Tonic NMDA receptor signalling shapes endosomal organisation in mammalian cells - Oleg O. Glebov (Nature Portfolio, 2020)
Abstract Calcium signalling through NMDA-type glutamate receptors (NMDARs) plays a key role in synaptic plasticity in the central nervous system (CNS). NMDAR expression has also been detected in other tissues and aberrant glutamate signalling has been linked to cancer; however, the significance of NMDAR function outside of the CNS remains unclear. Here, I show that removal of extracellular calcium rapidly decreases the size of early endosomes in primary human fibroblasts. This effect can be mimicked by blockade of NMDA-type glutamate receptors but not voltage-gated calcium channels (VGCCs), and can also be observed in primary hippocampal neurons and Jurkat T cells. Conversely, in a breast cancer cell line MDA-MB-231 NMDAR blockade results in an increase in endosomal size and decrease in number. These findings reveal that calcium signalling via glutamate receptors controls the structure of the endosomal system and suggest that aberrations in NMDAR-regulated membrane trafficking may be associated with cancer.